2017
DOI: 10.1103/physrevb.95.134303
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational properties and stability of FePt nanoalloys

Abstract: The structural and dynamical properties of FePt nanoparticles were studied within the density functional theory. The effect of size and chemical composition on dynamical stability of nanoparticles was investigated for the cuboctahedral and icosahedral symmetries. In cuboctahedra, the structural distortion is observed, which for systems with odd number of Pt layers leads to lowering of the tetragonal symmetry. Significant differences between the vibrational properties of FePt particles and bulk crystal is obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, while the spacing between disk and slider in devices with ultra-high magnetic density is remarkably reduced and their intermittent contact is highly probable, less attention has been paid to mechanical stability and to the strength of such films and their interfaces. To mention some of the relevant studies, nanoscratch experiments were performed by Liu et al [16] to study the effect of contact stress on the magnetic signal strength, first-principles calculations were employed to calculate cleavage energies for several crystallographic planes in bulk FePt [17] and to obtain generalized stacking fault energy [18] as well as phonon dispersions [19] in FePt nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, while the spacing between disk and slider in devices with ultra-high magnetic density is remarkably reduced and their intermittent contact is highly probable, less attention has been paid to mechanical stability and to the strength of such films and their interfaces. To mention some of the relevant studies, nanoscratch experiments were performed by Liu et al [16] to study the effect of contact stress on the magnetic signal strength, first-principles calculations were employed to calculate cleavage energies for several crystallographic planes in bulk FePt [17] and to obtain generalized stacking fault energy [18] as well as phonon dispersions [19] in FePt nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…38 However, the previous study did neither reach the temperatures showing any signs of melting nor present thermodynamical parameters of the systems. The lattice dynamics study, 55 investigating phonon DOS spectra of these systems, also exposed instabilities of nanoparticles with the iron core. However, stability at high temperatures was not addressed, since all calculations were done at 0 K. The present study is concerned with establishing the limits of thermal stability of these systems.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results 38,55 showed the instability of the Feterminated nanoparticles even at cryogenic temperatures. MD simulations indicate that they promptly reorganize and lose the structure.…”
Section: Pt-terminated Icosahedral Structurementioning
confidence: 87%
“…In comparison with bulk materials, nanocrystals show a wide range of size dependent effects including optical, magnetic, , catalytic, , and thermodynamic properties. With the development of nanocrystal based photonic and optoelectronic devices, stability becomes an urgent issue to initialize industrialization. , Temperature increase is a commonly observed phenomenon related to the thermal stability of nanocrystal devices. Specific heat capacity, termed as heat capacity per unit of mass, is one of the most fundamental thermodynamic properties of materials. , In principle, temperature increase is inversely proportional to heat capacity under certain conditions, which is a key parameter to design highly stable electronic devices. Early works and simulations have shown that the specific heat capacity of metal nanocrystals increases by 10% to 40% at low and room temperatures. The enhanced specific heat capacity of metal nanocrystals can be attributed to the increase of surface-to-volume ratio, which can explain the decrease of Debye temperature induced by extra surface phonons. In comparison, the specific heat capacity of semiconductor nanocrystals has received limited attention. Here, we report the size dependence in the specific heat capacity of colloidal PbSe nanocrystals.…”
mentioning
confidence: 99%